2023
DOI: 10.1038/s41550-023-01947-5
|View full text |Cite
|
Sign up to set email alerts
|

A history of mild shocks experienced by the regolith particles on hydrated asteroid Ryugu

Abstract: Micrometeorites, a possible major source of Earth’s water, are thought to form from explosive dispersal of hydrated chondritic materials during impact events on their parental asteroids. However, this provenance and formation mechanism have yet to be directly confirmed using asteroid returned samples. Here, we report evidence of mild shock metamorphism in the surface particles of asteroid Ryugu based on electron microscopy. All particles are dominated by phyllosilicates but lack dehydration textures, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
3
1
Order By: Relevance
“…Previously, ferrihydrite was thought to be produced by aqueous alteration in the CI parent body (Bullock et al, 2005;Tomeoka & Buseck, 1988). However, many recent studies reported that ferrihydrite is not present in fresh CI-like Ryugu particles (Ito et al, 2022;Nakamura, Kobayashi, et al, 2022;Nakamura, Matsumoto, et al, 2022;Tomioka et al, 2023;Yamaguchi et al, 2023;this study). In contrast, ferrihydrite is a common low-crystalline phase in terrestrial environments (e.g., Bigham et al, 1996).…”
Section: Discussion Terrestrial Weathering Observed In the Orgueil Ch...contrasting
confidence: 42%
See 1 more Smart Citation
“…Previously, ferrihydrite was thought to be produced by aqueous alteration in the CI parent body (Bullock et al, 2005;Tomeoka & Buseck, 1988). However, many recent studies reported that ferrihydrite is not present in fresh CI-like Ryugu particles (Ito et al, 2022;Nakamura, Kobayashi, et al, 2022;Nakamura, Matsumoto, et al, 2022;Tomioka et al, 2023;Yamaguchi et al, 2023;this study). In contrast, ferrihydrite is a common low-crystalline phase in terrestrial environments (e.g., Bigham et al, 1996).…”
Section: Discussion Terrestrial Weathering Observed In the Orgueil Ch...contrasting
confidence: 42%
“…The first-year analytical campaign of Ryugu particles, including mineralogy, petrology, and oxygen isotopes, confirmed the link between Ryugu particles and CI chondrites (e.g., Greenwood et al, 2022;Ito et al, 2022;Liu et al, 2022;McCain et al, 2023;Nakamura, Kobayashi, et al, 2022;Nakamura, Matsumoto, et al, 2022;Tomioka et al, 2023;Yamaguchi et al, 2023;Yokoyama et al, 2022). Because Ryugu particles are among the most uncontaminated solar system materials available for laboratory analysis on Earth (e.g., Ito et al, 2022;Yokoyama et al, 2022), they should be an excellent experimental example for tracking terrestrial weathering products (minerals) and the abundances of water over time under controlled conditions (i.e., temperature, humidity, and duration).…”
Section: Introductionmentioning
confidence: 72%
“…The pseudo-magnetites observed in the present study were not likely produced during the sampling operation by Hayabusa2 for the following reasons. The upper limit of the peak pressure experienced by Ryugu particles during sampling operations of Hayabusa2, in which a tantalum projectile was accelerated to 300 ± 30 m s −1 in the sampler horn 33 , was estimated to be only 1.3 GPa 34 . These events were not sufficient to heat the Ryugu particles to 300 K 8 .…”
Section: Resultsmentioning
confidence: 98%
“…Although a large number of impact craters were observed on the surface of current Ryugu [4,16], no evidence of such extreme conditions has been recognized, and low-temperature products such as phyllosilicates and OM are abundantly preserved in the Ryugu samples investigated so far [19,20,23,27,30]. The recently discovered microfault-like textures and the high-pressure polymorph of Fe-Cr sulfide in the Ryugu particles indicated that asteroid Ryugu has experienced mild shocks with the average peak pressure of <2 GPa [54], but this is unlikely to support an impact capable of shattering the Ryugu progenitor body. Alternatively, the high microporosity of the progenitor body, similar to that of a yarn ball, which consists mainly of phyllosilicates interconnected with nm-to µm-sized voids, might have precluded any record of intense impacts on Ryugu.…”
Section: Evolution To a Rubble Pile Asteroidmentioning
confidence: 97%